Titanium-containing slag treatment method and application

By adding slag additives to the titanium-containing furnace slag and subjecting to heating, water quenching and high-temperature roasting, impurities iron particles and harmful components are removed and converted into high-valent titanium oxides, it is solved that it is difficult to effectively utilize titanium-containing furnace slag in the prior art. The problem of this has achieved efficient utilization of titanium resources and improved performance of protection slag.

CN119456969APending Publication Date: 2025-02-18万杨知为
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411414355.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove harmful impurities in the titanium-containing furnace slag, making it unable to meet the requirements of traditional continuous casting protection slag or weak electrolyte protection slag, resulting in the inability to fully utilize titanium resources.

Method used

By adding slag additives (such as CaF2, CaO, MgO, SiO2, etc.) to the titanium-containing furnace slag, heating to a molten state, performing water quenching and high-temperature roasting, removing impurities, iron particles and harmful components, and converting low-valent titanium oxides. For the high-valent titanium oxide TiO2, titanium-containing slag powder suitable as a protective slag raw material is obtained.

Benefits of technology

It realizes effective removal of harmful impurities in titanium-containing furnace slag, improves the utilization rate of titanium resources, reduces the production cost of protective slag, and ensures the performance stability and product quality of protective slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005078953220000061
    Figure BDA0005078953220000061
Patent Text Reader

Abstract

The invention discloses a titanium-containing furnace slag treatment method and application thereof. The method comprises the following steps: 1) adding a certain amount of slag additive into the titanium-containing slag, and fully mixing to obtain a titanium-containing slag mixture; 2) heating the titanium-containing slag mixture to 1300-1600 DEG C to completely melt the titanium-containing slag mixture; (3) pouring the melt of the titanium-containing slag mixture into water for water quenching treatment, and (4) after drying slag particles, carrying out high-temperature roasting treatment at 700-1300 DEG C; and 5) grinding the slag particles into powder. The invention further provides application of the titanium-containing slag powder obtained through the titanium-containing slag treatment method in production of weak electrolyte covering slag or traditional continuous casting covering slag. According to the method, TiO2 in the titanium-containing slag is fully utilized, secondary utilization of resources is achieved, the method is used for producing the casting powder, it can be guaranteed that the casting powder is evenly melted and good in using effect, and the production cost of the casting powder is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel smelting, and in particular to a method for treating titanium-containing slag and application of the slag obtained after the treatment. Background Art

[0002] In steel smelting, titanium-containing iron ore blast furnace method is used to produce molten iron to form titanium-containing slag. Every 1t of pig iron smelted will produce about 220-370kg of titanium-containing slag, with a huge output. The titanium content in the slag is usually measured in TiO2. The current titanium-containing slag mainly includes high-titanium slag represented by Panzhihua Iron and Steel, whose TiO2 weight content is about 20-25%; and low-titanium slag represented by Chengde Iron and Steel, whose TiO2 weight content is about 7-10%. With the continuous improvement and improvement of smelting technology, the slag emissions of steel enterprises have decreased year by year, but due to the large scale of steel production capacity and the historical "debts" in environmental protection, the total amount of slag emissions is still relatively large. For example, the accumulation of titanium-containing slag in Panzhihua Iron and Steel has reached nearly 70 million tons, and its accumulation is still increasing at an average rate of 3.6 million tons / year. Due to the high titanium content in high-titanium slag, the titanium resources in Panzhihua Iron and Steel's high-titanium slag account for about 50% of the total titanium resources in Panzhihua area.

[0003] The titanium in titanium-containing slag is dispersed in various titanium-containing mineral phases such as perovskite, diopside, titanium-rich diopside, spinel and titanium carbonitride, and the embedding relationship is complex. Moreover, the grains of titanium-containing mineral phases dispersed in the slag are very small, with an average of only about 10μm. It is very difficult to separate and recover titanium using conventional mineral processing technology. There are problems such as high pollution, high energy consumption, low efficiency, small product market, and high cost, and it is impossible to form production capacity. Therefore, the utilization rate of titanium-containing slag is extremely low at present. Except for a small amount used as building materials, most of it is still piled up in the slag yard, resulting in serious waste of titanium resources. It is very meaningful to make full and reasonable use of the titanium resources in the slag.

[0004] At present, the traditional continuous casting protective slag system commonly used by steelmaking enterprises consists of three parts: base material, flux, and carbonaceous material. The flux is alkali metal oxides, alkali metal fluorides, boron oxides and other low-melting point substances, which can effectively reduce the melting point and viscosity of the protective slag. This traditional continuous casting protective slag is widely used. Application No. 201910961335.2 discloses a weak electrolyte protective slag, which is a new type of protective slag system. It does not contain alkali metal oxides, alkali metal fluorides, boron oxides and other low-melting point substances. There is no separation during use, the slag is uniform, and it has the characteristics of weak oxidation for steels containing aluminum, rare earths, titanium, etc., as well as the advantages of preventing moisture absorption. The weak electrolyte protective slag has been promoted and used in many steel mills such as Baosteel, and its technical effect advantages are obvious.

[0005] The main chemical composition of titanium-containing slag is the five-element slag system CaO-MgO-SiO2-Al2O3-TiO2, which can be used as raw materials for traditional continuous casting protection slag and weak electrolyte protection slag. Moreover, TiO2, as a new component, can also reduce the melting point and viscosity of the protection slag. However, research has found that titanium-containing slag also contains harmful components to the protection slag. These harmful components are dispersed in the slag as fine particles and are difficult to remove by simple physical methods. Its harmful components mainly include the following: 1) metallic iron, which contains about 1-3% of metallic iron in the slag. When the protective slag is used, it is oxidized, thereby changing the physical properties of the protective slag, while the unoxidized iron sinks into the molten steel, bringing in impurities and polluting the molten steel; 2) about 0.1-0.3% of free carbon and 0.5-1.0% of titanium carbonitride in the slag. Since carbon and titanium carbonitride are dispersed in the slag, if they are directly used as protective slag raw materials, they are not easily completely oxidized when the protective slag is used, resulting in a developed slag sintering layer; 3) low-valent titanium oxides TiO, Ti2O3, Ti3O5 and their composite oxides, which exist in uncertain contents in the slag. When analyzing the components in the slag, these low-valent titanium oxides are measured as TiO2, but their physical and chemical properties are quite different from those of TiO2, making the performance of the protective slag unstable.

[0006] Chongqing University's patent entitled "A fluorine-free protective slag of titanium-containing blast furnace slag and its manufacturing process" (publication number CN1481954A) discloses the use of Panzhihua Iron and Steel's TiO2-containing slag to produce protective slag, which uses TiO2 to form perovskite (CaTiO3) crystals in the fluorine-free protective slag, replacing the gunite (3CaO·2SiO2·CaF2) in the traditional continuous casting protective slag to control the heat transfer of the protective slag film in the crystallizer. The titanium-containing slag used in this patent has not been processed for its components, and the harmful components in it have side effects during the use of the protective slag, resulting in unstable performance of the protective slag and difficult to control product quality.

[0007] Therefore, when effectively utilizing titanium-containing slag to prepare traditional continuous casting protective slag or weak electrolyte protective slag for full and reasonable reuse of titanium resources, there is an urgent need for a method that can effectively remove harmful impurities in the slag so that the treated slag can fully meet the requirements of traditional continuous casting protective slag or weak electrolyte protective slag. Summary of the invention

[0008] The technical problem to be solved by the present invention is to treat the titanium-containing slag produced in the steel smelting process, remove harmful impurities therein so that it meets certain technical requirements, and use it as a raw material for traditional continuous casting protective slag or weak electrolyte protective slag.

[0009] The method for treating titanium-containing slag of the present invention comprises the following steps:

[0010] 1) adding a certain amount of slag additive to the titanium-containing slag and mixing thoroughly to obtain a titanium-containing slag mixture, wherein the slag additive is prepared from one or more of CaF2, CaO, MgO, and SiO2;

[0011] 2) heating the titanium-containing slag mixture to 1300-1600° C. to completely melt the titanium-containing slag; adding a slag additive to the titanium-containing slag to adjust the melting point and viscosity of the titanium-containing slag, so that the titanium-containing slag is molten at a lower temperature and the impurity iron particles are easier to aggregate, precipitate and separate;

[0012] 3) pouring the melt of the titanium-containing slag mixture into water for quenching, and solidifying the titanium-containing slag mixture into slag particles,

[0013] 4) After the slag particles are dried, they are subjected to high-temperature calcination at 700-1300° C. The high-temperature calcination is used to remove carbonaceous particles and Ti(CN) in the slag particles and convert low-valent titanium oxides into high-valent titanium oxides TiO2;

[0014] 5) The slag particles after the roasting treatment are ground into powder to obtain the treated titanium-containing slag powder, which is used as the protective slag raw material.

[0015] Any of the following schemes is a preferred scheme of the present invention:

[0016] Preferably, in step 1), the content of each component of the slag additive in the total weight percentage of the titanium-containing slag mixture is: CaF2 accounts for 4-20%, CaO accounts for 0.01-15%, MgO accounts for 0.01-8%, and SiO2 accounts for 0.01-20%. These slag additives are low in cost, can effectively reduce the melting temperature and viscosity of the melt, and are conducive to the precipitation of iron in the titanium-containing slag under high temperature.

[0017] Preferably, in step 1), the slag additive further comprises one or more of BaO, SrO, RExOy (mixed rare earth oxides), and ZrO2, wherein the weight percentage of each component in the total weight of the titanium-containing slag mixture is: BaO accounts for 0.01-8%, SrO accounts for 0.01-5%, RExOy accounts for 0.01-5%, x O y The titanium slag powder containing Na2O is used to produce conventional continuous casting protective slag.

[0018] Preferably, the titanium-containing slag mixture in step 2) is heated to 1400-1500° C. At this temperature, the titanium-containing slag mixture can reach a molten state and the melt has sufficient fluidity, which is conducive to the sedimentation and aggregation of iron particles;

[0019] Preferably, during the heating in step 2), air or oxygen is blown into the titanium-containing slag. This operation can not only play a stirring role, accelerate the aggregation and sedimentation of metallic iron particles, but also oxidize part of the free carbon, titanium carbonitride, and low-valent titanium oxide.

[0020] Also preferably, in step 4), the calcination temperature is 800-1100° C., which can ensure that the reaction in the slag proceeds quickly without causing the slag to sinter.

[0021] Also preferably, in step 4), the slag particles are dried, ground and then calcined, so that the calcination reaction speed is faster.

[0022] The present invention also provides the use of titanium-containing slag powder obtained by the method for treating titanium-containing slag in the production of weak electrolyte protective slag or traditional continuous casting protective slag, that is, adding protective slag auxiliary materials to the titanium-containing slag powder to make weak electrolyte protective slag or traditional continuous casting protective slag, wherein the titanium-containing slag powder accounts for 15 to 95% of the total weight of the protective slag, preferably 35 to 85%, and the protective slag auxiliary materials are one or more of fluorite, quartz, magnesium oxide powder, limestone powder, dolomite powder, sodium carbonate, barium carbonate, borax, and carbonaceous materials.

[0023] The basic principle of the titanium-containing slag treatment method of the present invention is:

[0024] 1) By adding a certain amount of slag additives to the titanium-containing slag: one or more of CaF2 (CaF2 is the source of F in the protective slag), CaO, MgO, SiO2, and further Na2O or BaO, SrO, RE x O y (mixed rare earth oxides), ZrO2 and other components, can significantly reduce the melting point and viscosity of titanium-containing slag, which is conducive to the aggregation and sedimentation of metal iron particles in the slag in the slag liquid, effectively reducing the iron content in the slag and shortening the processing time;

[0025] 2) Pour the melt into a large amount of cold water for water quenching, so that the slag is cooled quickly and the melt forms glassy particles, which are easy to crush and grind. At the same time, it can oxidize part of the free carbon and titanium carbonitride, and it is beneficial for oxygen to enter the interior of the particles during roasting, thereby improving the roasting efficiency.

[0026] 3) The slag particles are dried and then calcined at high temperature in a calcining furnace to completely oxidize and remove free carbon and titanium carbonitride in the slag, while completely converting low-valent titanium oxide into TiO2. The chemical equation for the calcining process is as follows:

[0027] TiO+O2=TiO2

[0028] 2Ti2O3+O2=4TiO2

[0029] 2TiN+2O2=2TiO2+N2

[0030] TiC+2O2=TiO2+CO2

[0031] C+O2=CO2

[0032] 4) Grinding the slag particles after calcination to obtain titanium-containing slag powder as a raw material for mold slag. Since the powder crystals change after calcination, the melting rate of the mold slag can be reduced, and the melting rate of the mold slag can be controlled by adding less or no carbonaceous material.

[0033] The beneficial effects achieved by the present invention are:

[0034] 1) The TiO2 in the titanium-containing slag is fully utilized, the secondary utilization of resources is realized, and the production cost of the protective slag is greatly reduced. If industrially purified TiO2 is used, its unit price is about 20,000 yuan / t. The use of this patent design to produce weak electrolyte protective slag using the treated titanium-containing slag has a cost advantage compared with ordinary slag;

[0035] 2) The treated titanium slag powder has uniform composition, which is equivalent to pre-melted material. It is used to produce protective slag, which can ensure uniform melting of the protective slag and good use effect. DETAILED DESCRIPTION

[0036] The treatment method of titanium-containing slag and its application are further described in detail below in conjunction with specific embodiments.

[0037] In the following examples, the raw materials used are all raw materials purchased publicly on the market. The grades of the slag additive raw materials purchased in each example are as follows:

[0038] Fluorite: CaF2>95%;

[0039] Quartz: SiO2>98%;

[0040] Limestone: CaO is about 54%;

[0041] Dolomite: CaO is about 30%, MgO is about 21%;

[0042] Sodium carbonate, barium carbonate, strontium carbonate, rare earth oxides, and ZrO2 are industrial pure;

[0043] In the following examples, the TiO2 content of the titanium-containing slag of Panzhihua Iron and Steel is about 23%, and the TFe content is about 3.2%; the TiO2 content of the titanium-containing slag of Chengde Iron and Steel is about 9%, and the TFe content is about 1.0%.

[0044] The titanium-containing slag treatment method of this embodiment comprises the following steps:

[0045] 1) Add a certain amount of slag additive to the titanium-containing slag and mix thoroughly to obtain a titanium-containing slag mixture. The components of the titanium-containing slag mixture obtained in each embodiment are as follows:

[0046]

[0047] In the table, MxOy=BaO+SrO+RExOy+ZrO2

[0048] 2) Add the titanium-containing slag mixture into a medium frequency electric furnace and heat it to 1450-1500°C until the slag is completely melted, introduce oxygen or air into the bottom of the electric furnace, and use mechanical stirring in the slag to accelerate the aggregation and sedimentation of metal iron particles;

[0049] 3) After the titanium-containing slag mixture is melted for 20 minutes, the melt is poured into a cold water tank for water quenching, and the titanium-containing slag mixture solidifies into fine slag particles;

[0050] 4) The slag particles formed in step 3) were ground to less than 200 mesh, and calcined in a high-temperature furnace at 1000°C for 30 minutes. The powder color changed from black to brown-yellow. XRD analysis showed that no C, TiN, or TiC was found.

[0051] 5) Collect the slag particles after roasting to obtain titanium-containing slag powder as a protective slag raw material.

[0052] Example 6

[0053] The titanium-containing slag powder obtained according to the ingredients of Example 1 was used as the raw material, and a certain amount of protective slag auxiliary materials such as fluorite and quartz was added to adjust the composition and performance, and 700 kg of hollow particle weak electrolyte carbon-free protective slag was produced, wherein the weight content of the titanium slag powder raw material treated by the method of the present invention accounted for about 63%, and the main physical and chemical indicators of the obtained weak electrolyte carbon-free protective slag were: F: 5.73%, CaO: 32.5%, MgO: 7.64%, SiO2: 36.9%, Al2O3: 4.38%, TiO2: 6.14%, C 固:0.10%; hemisphere point temperature: 1283℃, solidification temperature: 1010℃, viscosity: 0.46pas. A continuous casting production test was carried out in a steel plant for automobile plate steel. The test results show that no slag strips are produced during the whole process using the weak electrolyte carbon-free protective slag of this embodiment, the thickness of the liquid slag layer is 11-13mm and stable, the slab is basically free of common defects such as cracks, and the steel billet does not increase carbon. The use of the crystallizer and the surface quality of the casting are better than those of imported protective slag and other domestic protective slags. The protective slag has been officially put into production and application in a steel plant.

[0054] The reason why this protective slag does not produce slag strips during the use process is that the raw materials are all high-melting-point materials, and no separation phenomenon will occur during melting. This is the characteristic of weak electrolyte protective slag.

[0055] Example 7

[0056] The titanium-containing slag powder obtained in Example 2 was ground to less than 300 meshes as raw material, and a certain amount of fluorite, quartz, magnesium oxide powder, barium carbonate, carbonaceous material and other protective slag auxiliary materials were added to adjust the composition and performance, and 800 kg of hollow particle weak electrolyte protective slag was produced, wherein the weight content of the titanium slag powder raw materials treated by the method of the present invention accounted for about 52%, and its main physical and chemical indicators were: F: 7.2%, CaO: 35.8%, MgO: 8.5%, SiO2: 33.6%, Al2O3: 5.9%, TiO2: 5.5%, BaO: 6.0%, C 固 : 1.6%; hemisphere point temperature: 1255℃, solidification temperature: 1025℃, viscosity: 0.28pas. A continuous casting production test was conducted on a high-grade non-oriented silicon steel in a CSP plant. The test results showed that there was no slag in the mold, the thickness of the liquid slag layer was 7-9mm, and the cracks in the slab and the plate after rolling were less than the imported protective slag used before.

[0057] Example 8

[0058] The titanium-containing slag powder obtained in Example 3 was ground to less than 300 meshes as raw material, and a certain amount of fluorite, quartz, dolomite powder, carbonaceous material and other protective slag auxiliary materials were added to adjust the composition and performance, and 800 kg of hollow particle weak electrolyte protective slag was produced, in which the weight content of the titanium slag powder raw material treated by the method of the present invention accounted for about 45%, and its main physical and chemical indicators were: F: 9.6%, CaO: 28.1%, MgO: 7.1%, SiO2: 30.2%, Al2O3: 8.5%, TiO2: 4.5%, C 固 : 1.4%; hemisphere point temperature: 1161℃, solidification temperature: 1005℃, viscosity: 0.23pas. A continuous casting production test of non-oriented silicon steel was carried out in a CSP plant. The test results showed that there was no slag in the mold, the thickness of the liquid slag layer was 5-8mm, and the quality of the slab and the plate after rolling was better than that of the domestic mold slag used at the same time.

[0059] Example 9

[0060] The titanium-containing slag powder obtained in Example 4 is ground to less than 200 mesh as raw material, and a certain amount of protective slag auxiliary materials such as fluorite, quartz, and carbonaceous materials are added to adjust the composition and performance, and 1000 kg of weak electrolyte protective slag is produced, in which the weight content of the titanium slag powder treated by the method of the present invention accounts for about 63% of the raw material weight. It is applied to low-carbon steel slabs. The protective slag performs well in the crystallizer and the quality of the casting is good.

[0061] Example 10

[0062] The titanium-containing slag powder obtained in Example 5 is ground to less than 300 mesh as raw material, and a certain amount of fluorite, sodium carbonate, quartz, carbonaceous material, etc. are added to adjust the composition properties, and 500 kg of traditional continuous casting protective slag is produced, in which the weight content of the titanium slag powder raw material treated by the method of the present invention accounts for about 55%. It is used in CSP low-carbon steel, and the billet drawing speed is 5.2 m / min. The results of use are as follows: there is no slag strip in the protective slag in the crystallizer throughout the whole process, the thickness of the liquid slag layer is 6-8 mm, and there are few cracks in the slab and the plate after rolling.

Claims

1. A method for treating titanium-containing slag, comprising the following steps: 1) adding a certain amount of slag additive to the titanium-containing slag and mixing thoroughly to obtain a titanium-containing slag mixture, wherein the slag additive is prepared from one or more of CaF2, CaO, MgO, and SiO2; 2) heating the titanium-containing slag mixture to 1300-1600°C until it is completely melted; 3) pouring the titanium-containing slag mixture melt into water for quenching, and solidifying the titanium-containing slag mixture into slag particles, 4) After the slag particles are dried, they are calcined at 700-1300°C. 5) The slag particles after the calcination treatment are ground into powder to obtain titanium-containing slag powder.

2. The method for treating titanium-containing slag according to claim 1, characterized in that: In step 1), the content of each component of the slag additive in the total weight percentage of the titanium-containing slag mixture is: CaF2 accounts for 4-20%, CaO accounts for 0.01-15%, MgO accounts for 0.01-8%, and SiO2 accounts for 0.01-20%.

3. The method for treating titanium-containing slag according to claim 1 or 2, characterized in that: In step 1), the slag additive also contains a certain amount of one or more of BaO, SrO, RExOy, and ZrO2, wherein the weight percentage of each component in the total weight of the titanium-containing slag mixture is: BaO accounts for 0.01-8%, SrO accounts for 0.01-5%, RExOy accounts for 0.01-5%, x O y It accounts for 0.01-3.5%, ZrO2 accounts for 0.01-3.5%, and the total weight of BaO, SrO, RExOy, and ZrO2 accounts for 3-15% of the total weight of the titanium-containing slag mixture.

4. The method for treating titanium-containing slag according to claim 1 or 2, characterized in that: In step 1), the slag additive also contains a certain amount of Na2O, and the Na2O accounts for 3-12% of the total weight percentage of the titanium-containing slag mixture.

5. The method for treating titanium-containing slag according to claim 3, characterized in that: In step 1), the slag additive further contains Na2O, and the Na2O accounts for 3-12% of the total weight percentage of the titanium-containing slag mixture.

6. The method for treating titanium-containing slag according to claim 1 or 2, characterized in that: In step 2), the temperature of the titanium-containing slag mixture is raised to 1400-1500°C.

7. The method for treating titanium-containing slag according to claim 1 or 2, characterized in that: During the heating in step 2), air or oxygen is blown into the titanium-containing slag.

8. The method for treating titanium-containing slag according to claim 1 or 2, characterized in that: In step 4), the calcination temperature is 800-1100°C.

9. An application of the titanium-containing slag powder obtained by the method of claim 1 in the production of weak electrolyte mold slag or conventional continuous casting mold slag, characterized in that: The titanium-containing slag powder is added with protective slag auxiliary materials to make weak electrolyte protective slag or traditional continuous casting protective slag, wherein the titanium-containing slag powder accounts for 15 to 95% of the total weight of the protective slag, and the protective slag auxiliary materials are one or more of fluorite, quartz, magnesium oxide powder, limestone powder, dolomite powder, barium carbonate, sodium carbonate, borax, and carbonaceous materials.

10. The use of the titanium-containing slag powder according to claim 9 in the production of weak electrolyte protection slag or traditional continuous casting protection slag, characterized in that: The titanium-containing slag powder accounts for 35-85% of the total weight of the protective slag.

Citation Information

Patent Citations

  • Weak electrolyte casting powder

    CN110548842A

  • Fluorine-free environment-friendly type continuous casting protecting slag for the blast furnace slag containing titanium and the manufacturing process of the same

    CN1481954A